Children's digital storymaking - The negotiated nature of instructional literacy events - Ewa Skantz Åberg; Annika Lantz-Andersson; Niklas Pramling (Universitetsforlaget, 2015)
Narrative is used in early childhood education to engage children in reading and writing. With the advent of digital technologies, new contexts are created for multimodal ways of narrating. The purpose of this study is to illuminate the relationship between a digital storymaking activity and the stories made in an early years practice. The results show that the children's texts to varying degrees approximate a narrative genre and illustrate how these variations can be understood in terms of how the participants negotiate the task.